PSInSAR remote sensing observations of deformation behaviour at Salisbury Plain, UK - Agar,S; Lawrence,J; Ghail,R; Mason,P; Thompson,S (ICE Publishing, 2018)
PSInSAR is a radar remote sensing approach that offers measurements of ground deformation over large areas at sub-mm precision. The technique has significant potential for granting insight into ongoing geological processes. Data recovery in rural areas is challenging due to the highly inconsistent radar scattering behaviour exhibited by vegetated ground, and thus a rural area of the UK – Salisbury Plain - was used as a case study to examine the challenges and potential for PSInSAR techniques in rural areas. Results showed regional uplift of clay formations relative to the Chalk, which was attributed to clay shrink-swell correlated with seasonal increases in groundwater levels.